Bexarotene signaling in human B and T lymphocytes induces gut-homing receptor expression - Kaiser, Sina; Suhrkamp, Ina; He, Jinru; Helf, Charlotte; Sadik, Christian D.; Weichenthal, Michael; Heine, Guido (Frontiers in Immunology, 2025)
BackgroundRetinoic acid (RA) receptors (RARs) in human lymphocytes modulate the humoral and intestinal immune response by regulating target genes, including CD38, TGM2, and gut-homing markers. The impact of retinoid X receptors (RXRs) on this process is elusive.ObjectiveTo determine the impact of the RXR ligand bexarotene (BXR) on the activation and differentiation of human B and T lymphocytes.MethodsIn vitro BXR stimulation of human CD19+ B cells and CD4+ T helper cells was investigated regarding retinoid target gene expression using qPCR and flow cytometry and validated in peripheral B and T lymphocytes of patients with cutaneous T-cell lymphoma (CTCL) with and without BXR treatment.ResultsBXR induced the canonical retinoid target gene CD38 in B cells and T cells (sixfold and threefold, respectively). BXR increased CD38 surface protein expression on B cells twofold and plasmablast differentiation threefold. The frequency of the gut-homing receptors CCR9 and integrin β7 was doubled on T and B cells after BXR stimulation, while cutaneous leucocyte-associated antigen (CLA) expression was decreased in B cells. Under BXR treatment, a reduced frequency of cells with these gut-homing receptors was observed in the blood of CTCL patients regarding memory T cells (mean off: 1.9%; on: 0.6%) and B cells (mean off: 5.7%, on: 4%).ConclusionBXR via RXRs directly targets B and T lymphocytes, inducing retinoid target gene expression, including gut-homing receptors.